Water quality effects on the bubble-particle attachment of sulfide minerals - October, Lisa Louise (Department of Chemical Engineering, 2022)
probability, mass of particles recovered in the ACTA and further validation with microflotation recovery that bubble-particle interaction increases as the ionic strength of the plant water increases. This was the case with both chalcopyrite and galena particles. Literature would suggest that this result of an increase in particle recovery and bubble-particle attachment may be due to the increase in concentration of inorganic electrolytes; which leads to the compression of the electrical double layer and the subsequent faster rupturing of the film at the air – water and solid – water interfaces resulting in faster bubble-particle attachment. Zeta potential measurements showed that the surface charge of the particles became less negative as the ionic strength of the water increased; this indicates the adsorption of cations on the particle surface. Furthermore, at the pH these tests were conducted (pH 6.5 to 7), the surface potential was closer to 0 mV as the ionic strength increases. A surface charge of 0 mV is known to result in particle agglomeration; therefore, in addition to faster rupturing of the film between the bubble and particle, particle agglomeration may also be responsible for the increase in bubble-particle attachment with increasing ionic strength of the plant water. Adsorption studies across all minerals showed that less xanthate adsorbs on the mineral surface as the ionic strength of the plant water increases; this indicates that the increase of inorganic electrolytes hindered xanthate adsorption on the mineral surface. Intuitively it is expected that this decrease in xanthate adsorption with water of higher ionic strength will translate to lower recoveries and bubble-particle attachment; the opposite was shown to be the case. The effect of the synthetic plant waters at pH 11 on bubble-particle attachment was also studied in this work. Zeta potential measurements showed a distinct increase in surface charge of all minerals with the three waters at pH 11; it was thus thought to be of interest to investigate this effect on bubble-particle attachment. Speciation diagrams of these waters show oxyhydoxyl constituents present at pH 11. Therefore, the presence of these species on the mineral surface is the reason for the increase in mineral surface charge. At pH 11, poor mineral recoveries regardless of the water type were observed as compared to the recovery with these waters at the natural pH (pH 6.5 to 7). It can thus be concluded that these oxyhydroxyl species hinder the flotation of the pyrrhotite particles as well as processes such as collector adsorption and the action of the electrical double layer. Another objective of this study was to ascertain whether certain ions within the plant water existed that either have a negative or positive effect on the bubble-particle interactions. If it is the case that one specific ion has a negative effect on bubble-particle attachment, then the removal of this ion would be a more cost effective and environmentally friendly exercise compared to treating the water or bringing in fresh water. Microflotation and ACTA studies with chalcopyrite, galena and pyrrhotite showed that Ca2+ containing solutions resulted in lower recoveries and attachment probabilities respectively. While the NaNO3 solution resulted in the highest recoveries and attachment probabilities across the three sulfide minerals. These results were observed both in the presence and absence of SIBX. Studies in literature have shown that the stability of the hydration layer in monovalent solutions of high ionic strength result in shorter induction times and thus improved bubble-particle attachment. This study also showed that the monovalent Na+ showed higher attachment probability and mineral recovery. Less xanthate was adsorbed on the sulfide mineral surfaces in Ca2+ containing solutions, hence the poorer bubble-particle attachment with the fundamental attachment timer and microflotation systems. The increased zeta potential and therefore high surface charge on the mineral surface in Ca2+ containing solutions may hinder the adsorption of xanthate as other authors have proposed that the collector adsorption reaction is driven by the electrical double layer and high surface charges may hinder this reaction. Therefore, it may be that the passivation of Ca2+ on the mineral surface may hinder the action of collector; as Ca2+ may compete with collector ions for sites on the mineral or that the high surface charge may be hindering the collector – mineral reaction. This work produced a number of outcomes. The validation of the use of the ACTA as a means of measuring mineral floatability through comparison with classical microflotation tests was displayed. The importance of showcasing both the attachment probability and mass of particles collected when taking measurements with the ACTA was evident in this work. This work also showed that the performance of bubble-particle attachment under ionic solutions was attributed to underlying factors such as the surface charge and collector – mineral adsorption. The adsorption of xanthate decreased in waters of high ionic strength and Ca2+ containing solutions. Waters of higher ionic strength further resulted in more positive surface potential and possible particle agglomeration resulting in higher recoveries. Bubble-particle attachment was also seen to reduce dramatically at pH 11 under the various synthetic plant waters; this was attributed to the presence of oxyhydroxyl species depositing on the mineral surface inducing surface hydrophilicity. Ca2+ was identified as resulting in lower mineral recoveries and attachment probabilities; Ca2+ passivated the sulfide minerals' surface more than Na+ and less collector adsorbed on the mineral surface in the presence of this ion. The latter result alludes to the fact that higher attachment probabilities and recoveries may be achieved by the removal of Ca2+ in recirculated plant water. The ACTA was constructed with the intent of it being a quick diagnostic tool on flotation plants to assess the bubble-particle efficiency under varying conditions; the outcome of this work showed that this instrument is a viable option as a measure for particle floatability. It is further believed that the findings of this work will provide flotation operations with an understanding of how specific ions within plant water affect bubble-particle attachment; which will allow for the water quality to be tailored towards achieving high mineral recoveries.